EVALUASI PASCA HUNI KEBERLANJUTAN PERUMAHAN MURAH TERHADAP PEGAWAI NEGERI SIPIL (PNS) - Nugroho, Fery Setyo; Marsoyo, Agam (LPPM Universitas Terbuka, 2022)
In 2019, Indonesia was experiencing a housing backlog of around 7.6 million housing that must bemet by providing new houses. Therefore there was a policy to overcome it through “one millionhousing” program. Salatiga City is one of the cities in Indonesia as a pilot project which hasconstructed provision of low-cost housing. While the current problem condition that happens is somefacilities and infrastructure were unconstructed yet. Low-cost housing provision is just focused onhousing units neglecting housing facilities and infrastructure that provided services for residents inpost-occupancy. This research aims to assess the performance of residential housing and examinethe gap factors influencing sustainability from a post-occupancy evaluation (POE) of low-cost housingprojects. This research was conducted by assessing performance factors influencing sustainabilityby POE to value the quality of the residential environment. The result showed that factors includingutility conditions; safety comfortability; social interactions; and access to workplace have goodperformance. While other factors have not met the score for good performance. This research hasknown that low-cost housing for civil servants can be said as unsustainable. The environmentalaspect had an important role in the sustainability of low-cost housing. Building unit condition,infrastructure and neighborhood facility are factors with a big importance in influencing sustainabilityof environmental aspect. Therefore, these factors need to get the main attention in the government’snext low-cost housing development projects in supporting one million housing program policy.